2020
DOI: 10.1128/jvi.01979-19
|View full text |Cite
|
Sign up to set email alerts
|

Co-opted Cellular Sac1 Lipid Phosphatase and PI(4)P Phosphoinositide Are Key Host Factors during the Biogenesis of the Tombusvirus Replication Compartment

Abstract: Positive-strand RNA [(+)RNA] viruses assemble numerous membrane-bound viral replicase complexes (VRCs) with the help of viral replication proteins and co-opted host proteins within large viral replication compartments in the cytosol of infected cells. In this study, we found that deletion or depletion of Sac1 phosphatidylinositol 4-phosphate [PI(4)P] phosphatase reduced tomato bushy stunt virus (TBSV) replication in yeast (Saccharomyces cerevisiae) and plants. We demonstrate a critical role for Sac1 in TBSV re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 108 publications
(174 reference statements)
0
26
0
Order By: Relevance
“…Another critical host protein in vMCS formation/function is Sac1p PI4P phosphatase, which allows the directional transfer of sterols from ER to the acceptor membranes through converting PI(4)P phosphoinositide to PI phosphatidylinositol [35]. PI(4)P is used by oxysterol localization of RFP-AtTim21 with the BiFC signal, indicating that the interactions between p33 replication protein and AtFis1A/B occur in the large viral replication compartments consisting of aggregated mitochondria.…”
Section: Interaction Between the Host Fis1 Protein And Sac1 Pi4p Phosmentioning
confidence: 99%
See 2 more Smart Citations
“…Another critical host protein in vMCS formation/function is Sac1p PI4P phosphatase, which allows the directional transfer of sterols from ER to the acceptor membranes through converting PI(4)P phosphoinositide to PI phosphatidylinositol [35]. PI(4)P is used by oxysterol localization of RFP-AtTim21 with the BiFC signal, indicating that the interactions between p33 replication protein and AtFis1A/B occur in the large viral replication compartments consisting of aggregated mitochondria.…”
Section: Interaction Between the Host Fis1 Protein And Sac1 Pi4p Phosmentioning
confidence: 99%
“…Another proposed important function of vMCS is to provide PI(4)P phosphoinositide for the OSBP-like oxysterol transfer proteins to drive the directional sterol exchange between the opposing membranes [75][76][77][78][79]. We have previously shown that TBSV co-opt the Stt4p PI4K kinase to VROs to produce PI(4)P, which is critical for VRO biogenesis [35]. To test if Fis1p affects the subcellular distribution of Stt4p PI4K during TBSV replication, we used fis1Δ yeast expressing the viral replication proteins.…”
Section: Plos Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Tomato bushy stunt virus (TBSV) and the closely related cucumber necrosis virus (CNV) use peroxisomal membranes, whereas carnation Italian ringspot virus (CIRV) exploits the outer membranes of mitochondria. The ER also contributes to VRO formation [ 16 18 ] and ER membranes even support TBSV replication efficiently in the absence of peroxisomes [ 19 ]. TBSV, similar to other (+)RNA viruses, induces major metabolic and structural changes in the infected cells, including aggregation of peroxisomal and ER membranes, membrane deformations by forming hundreds of 40–70 nm spherules that harbor the VRCs [ 6 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, over 100 yeast proteins were shown to interact with P33 or P92 and approximately 400 host proteins that could negatively or positively affect TBSV replication or recombination were identified [ 11 ]. These vast number of co-opted proteins comprise cellular translation factors, heat shock proteins, DEAD-box helicases, lipid biosynthesis and transfer enzymes, cytoskeleton components and even cellular energy-metabolism enzymes that altogether are reprogrammed to provide the optimal intracellular environment for TBSV replication [ 11 , 12 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%